Representasi Maskulinitas Iklan Joe Taslim X Fadil Jaidi Versi â€œSiapakah BA Head and Shoulders Selanjutnya?â€ - Findy Pattimah; Johantan Alfando WS (Universitas Batanghari Jambi, 2023)
The purpose of this research is to analyze the representation of masculinity and the meaning of myths contained in Joe Taslim X Fadil Jaidi advertisement for the version â€œSiapakah BA Head & Shoulders Selanjutnyaâ€. This research method uses interpretive qualitative methods with Roland Barthes' Semiotics analysis technique. The focus of this research is the characteristics of masculinity proposed by Beynon. The object of this research is the scenes in the advertisement for Joe Taslim X Fadil Jaidi's version of